Prevalence and Characteristics of Forward Head Posture among University Students - Lukman Faishal Fatharani; Rina Purnamasari; Mohammad Raihan Diki Ramadhan; Galih Prakasa Adhyatma (Journal of Public Health and Pharmacy)
Introduction: Forward head posture (FHP) is a condition of misalignment in the cervical vertebrae where the cervical spine shifts towards a more anterior angle. This change induces stress on the surrounding anatomical structures, leading to comorbidities and pathology. FHP has been identified as prevalent among young adults. Various risk factors contribute to this demographic's high burden of FHP, including increased exposure to modern technologies, such as smartphones. Therefore, our study aims to investigate the prevalence of FHP among university students in our center and analysed risk factors associated with FHP.